The relationship between job satisfaction and commitment among employees at Employees Provident Fund (EPF) headquarters / Noorazriena Omar (Faculty of Business Management, 2007)
Employee Provident Fund (EPF) was created as a mandatory national saving plan in 1951 and has grown consistently. This paper will study about the relationship between job satisfaction and commitment among employees at EPF Headquarters. I proposed the commitment as dependent variable and job satisfaction as independent variable. To measure the level of employee commitment, 3 factors will be analyzed which is (1) affective commitment (2) normative commitment and (3) continuous commitment. In order to measuring the level of job performance, five (5 ) factors will be used which are (1) pay (2) benefit (3) promotion (4) supervision (5) relationship with co - workers. Commitment of employee is very important for EPF because this organization strive to be a leader in the social security industry in the world and to be the best government agency in Malaysia. Employee will play an important role to make the vision of EPF become reality in the future. The main objective of this research is to determine the level of job satisfaction and commitment among employees and the relationship between job satisfaction and commitment among employees at EPF headquarters. Respondents of this study will be gathered from EPF headquarters staff and the data collected through questionnaires that will distribute to the 13 departments in EPF headquarters. About 100 respondents are chosen by using systematic sampling to answer the questionnaire. The data then will be analyzed by using SPSS. After the data analyzed, it is shows that there is a weak relationship between job satisfaction and commitment.